COUNSELING: IMPROVING HYPERTENSION HANDLING BEHAVIOR IN THE PUBLIC - Mahyuvi, Tata; Prasetyo, Joko; Puspitasari, Yenny; Amar, Munif; Kristiya Marta, Dony (Jurnal Abdi Masyarakat, 2023)
Hypertension is a non-communicable disease which is a very serious health problem and the main cause of death throughout the world. This community service aims to increase knowledge of how to treat hypertension through education to the community. Service activities were carried out on Tuesday 21 March 2023 at Mitra Medika Bondowoso Hospital using lecture and discussion methods. with 25 participants to find out about hypertension in patients. The way to find out knowledge related to hypertension prevention and control behavior used in community service activities is to ask and answer questions directly to patients. Before being given education in the form of health education about asthma, participants were given a question and answer session and after delivering the material a question and answer session was held to find out the participants' knowledge about hypertension. The evaluation results showed that participants understood hypertension. Public knowledge about hypertension is increasing and people are motivated to get access to treatment and knowledge about how to recognize and prevent hypertension after health education is carried out. It is hoped that this community service activity can be carried out continuously to increase public knowledge regarding various other health problems.